First record of tribe Laenini (Coleoptera, Tenebrionidae, Lagriinae) from Shanghai, with description of a new species of the genus Laena Dejean - Song, Xiao-Bin; Zhou, De-Yao; Chen, Zhi-Bing; Lin, Ming-Zhen; Zhu, Jian-Qing (Zootaxa, 2019)
Laena hongqiao sp. n. is described from Shanghai. This discovery expands the provincial distribution of the huge tenebrionid genus Laena in mainland China, and enriches the knowledge of the species diversity in Shanghai. A key modified from Schawaller 2008 and Wei & Ren 2018 is provided to include this new species.